Attention to the health of the LGBTQIA+ population aiming the integral access to health services (Research, Society and Development, 2022)
Introduction: In this study, the problematization and signaling of the state of the art on comprehensive care and the accessibility of the LGBTQ population to health services were aimed at. Also, the nod of the barriers faced by the population in the face of prejudice, stigma and marginalization. Methods: This is an integrative literature review study, with document analysis, exposition of the state of the art in a synoptic table, and discussion through thematic pillars. Results and Discussion: After the analysis of the eight articles, the confrontations and the difficulty of access to the health system services by the population in question became noticeable. It is highlighted that problems in welcoming the LGBT population in health services have been the agenda of the movement and NGOs, in the face of strong stigmatization, elements of homophobia, and misinformation regarding the specificities and rights of this population. Final Considerations: It is concluded that knowledge about health policies for the LGBT public must have its propagation expanded, so that one can deal with the spontaneous demand in health services and with the extinction of inequities.